Attachment in Marketing: An Exploratory Study of the Role of Social Media in the Creation of an Emotional Bond Between Luxury Fashion Brands and Consumers - Isik, Gizem (2014)
This dissertation aims to understand the role of social media in the creation of an emotional bond between consumers and luxury fashion brands along with the ways to create, maintain or enhance the bond. The influence of consumers’ interest in and use of social media to their attachment with luxury brands is also aimed to be pointed. Considering the subjective nature of personal feelings and its influence on the research, semi-structured interviews with open-ended questions were employed. By using purposive sampling technique in order to obtain data that will answer the research questions, twelve luxury brand followers were chosen to take part in the interviews. This study supports and confirms certain characteristics of attachment, social media and luxury brands pointed in the literature review. It also discovers the emotional aspects emerged through following luxury brands’ social media accounts. Getting closer with the brand was found to be the main effect of following a luxury brand rather than an emotional bond. This was the result of getting to know the brand more and realizing that the luxury brand cares about their consumers.